4, 6-Di-O-Benzylidenyl group-directed preparation of 2-deoxy-2-azido-α-d-galactopyranosides promoted by 3-O-TBDPS. (February 2021) - Liang, Xing-Yong; Yang, Jing; Qiu, Zhong-Hao; Wang, Lei; Lowary, Todd L.; Shawn Fan, Hua-Jun
Abstract: In this study, we designed a method to prepare 2-deoxy-2-azido-α-d -galactopyranosidic bonds using 4, 6-di-O-benzylidenyl-3-O-t-butyldiphenylsilyl protected 2-deoxy-2-azido-1-thio-d -galactopyranoside 5 as donors. The donor 5 gives a good to excellent α-selectivity in the glycosylation with secondary alcohols, which was found to be associated with the benzylidenyl on 4, 6-di-O and TBDPS on 3-O of the donor 5 . Compared with results of the donor 6 and 7, the 3-O-TBDPS could increase the activity of the thioglycoside, and the lone pairs on 4, 6-di-O-benzylidenyl group enhanced the gg-cofnormation, which plays a role in improving the stereoselectivity. Finally, this method was demonstrated through the synthesis of a α-galactosamine -containing pentasaccharide 26 . Graphical abstract: Image 1 Highlights: Stereocontrolled synthesis of 2-deoxy-2-azido-a-D-Gal p. Silyl ether improve the donor reactivity. Synthesis of a pentasaccharide.